Simultaneous Integrated Boost Intensity-Modulated Radiotherapy for Locally Advanced Drug-Resistant Gastrointestinal Stromal Tumors: A Feasibility Study - Li, Longhao; Yi, Xin; Cui, Haixia; Zhao, Xuemei; Dang, Jun; Jiang, Qingfeng; Li, Ying (Frontiers in Oncology, 2020)
Background As an emerging clinical problem, locally advanced drug-resistant gastrointestinal stromal tumors (LADRGISTs) has relatively few therapeutic schemes. Although radiotherapy is not often considered for GISTs, it could be a valuable contributing modality. The aim of our study is to explore a safe and effective radiation regimen for LADR-GISTs. Methods Three patients with LADR-GISTs were treated with simultaneous integrated boost intensity-modulated radiation therapy (SIB-IMRT) plans. In the SIB-IMRT plans, gross target volume (GTV) was divided into GTV-outer, GTV-mid, and GTV-center. And the prescribed dose of planning gross target volume (PGTV) and GTV-outer were both set to 50.4 Gy in 28 fractions. GTV-mid and GTV-center were simultaneously boosted to 60–62 Gy and 62–64 Gy respectively. For comparison purposes, conventional IMRT (Con-IMRT) plans with uniform dose distribution were generated for same optimization objectives without a dose boost to GTV-mid and GTV-center. All plans were optimized to make sure that deliver at least 95% of the prescription dose was delivered to PGTV. Isodose distribution, dose profiles, conformity indexes (CIs), monitor units (MUs), and dose volume histogram (DVH) was evaluated for each individual patient. After the three patients were treated with SIB-IMRT plans, the relative changes in the tumor size and CT values by CT scanning were also tracked. Results Compared with Con-IMRT plans, SIB-IMRT plans saw a significant increase from D95 to D2 of the GTV. With steeper dose gradients in the dose profiles, SIB-IMRT plans had GTV-mid and GTV-center accumulated with higher dose mainly by delivering extra 93 MUs in average. However, there was no significant difference in CIs and organs at risks (OARs) DVH. The relative changes in tumor size and CT values of the three patients in follow up were up to the Choi criteria and the three patients were all assessed as partial response. Conclusions The proposed SIB-IMRT may be a potential technique for achieving objective response and prolonging survival of selected GISTs patients.